Field Recording Approach of Traditional Music Arts for Ruwatan Bumi G20 Culture Performance: A Case Study in West Java - Simanjuntak, Jack Arthur (PANGGUNG, 2024)
The Ruwatan Bumi ceremony, part of the G20 Culture Ministers Meeting and Indonesia Festival Bertutur 2022, took place at Borobudur Temple, Central Java, in September 2022. Featuring a traditional ruwatan ritual, the event showcased live prayers, songs, and music from diverse Indonesian regions. Recording traditional music, vital for performance and rehearsal, was undertaken through a field recording approach. Beluk, tarawangsa, and Ronggeng Gunung were recorded using stereo and close-range methods. Employing a descriptive qualitative approach, the study emphasized the significance of mastering recording techniques for informed decision-making. It highlighted the coherence between initial information, field observations, and recording quality in designing the Ruwatan Bumi G20 Culture performance.